Nucleating acoustic cavitation with optically heated nanoparticles - Roy, RA (AIP Publishing, 2006)
The utilization of cavitation in high intensity focused ultrasound (HIFU) therapy requires the presence of nucleation sites; nucleation threshold pressures in tissues can exceed 4-5 MPa. We investigate the efficacy of transient vapor cavity generation from laser-illuminated gold nanoparticles as a means for nucleating cavitation. An acrylamide tissue phantom seeded with 82-nm diameter gold particle was exposed to 5 ns pulses from a 532 nm Nd:Yag laser. Acoustic emissions from inertial cavitation were detected by a 15 MHz broadband focused transducer at a laser energy of 0.10 mJ/pulse and a HIFU peak-negative focal pressure as low as 0.92 MPa. In comparison, a peak-negative focal pressure of 4.50 MPa was required to nucleate detectable cavitation without laser illumination. A simple analysis reveals that vapor cavities are formed that grow to the Blake radius, at which point they undergo rapid expansion and collapse. © 2006 American Institute of Physics.